Plant Growth, Nitrogen Content, Nitrogen Uptake, and Seed Quality in Six Bambara Groundnut (Vigna subterranea (L.) Verdc) Landraces - Rosyad, Astryani; Ilyas, Satriyas; Qadir, Abdul; Suhartanto, M Rahmad; Sopandie, Didy (Department of Agronomy and Horticulture, IPB University, 2025)
Bambara groundnut (Vigna subterranea (L.) Verdc) is recognized for its nutritional benefits and ability to improve soil fertility through nitrogen fixation. This study evaluated growth performance, nitrogen dynamics, and seed quality across six landraces: Tasikmalaya, Sukabumi, Sumedang, Small Sumedang, Bogor, and Gresik. The experiment was conducted at IPB University’s Sawah Baru experimental field from July 2022 to March 2023. The experiment used a randomized complete block design with four replications. The measured variables were petiole length, number of petioles, number of leaves, leaf greenness, plant dry weight, nitrogen content, nitrogen uptake in roots, petioles, leaves, and pods, protein content in pods, and seed quality. Results showed significant variation among landraces. Gresik exhibited superior vegetative growth and dry biomass, while Tasikmalaya had the highest pod nitrogen (4.58%) and protein content (28.03%), indicating efficient nitrogen assimilation. Nitrogen analysis revealed distinct uptake patterns across landraces, particularly with Gresik, where a rapid increase in nitrogen suggests that this landrace is well-suited to environments where nitrogen is efficiently fixed and mobilized toward reproductive growth. Sukabumi and Bogor showed the highest germination rates (94%), and Bogor and Gresik had the highest vigor indices (76% and 72%). Overall, Gresik is recommended for balanced performance in growth and seed vigor, while Tasikmalaya is optimal for protein yield and nitrogen use efficiency.